Organic Smart Home - Energiemanagement für Intelligente Gebäude - Allerding, Florian (KIT Scientific Publishing, 2013)
The Organic Smart Home is a generic framework as well as a runtime environment for the application in real smart homes to cope with the challenges of a flexible and adaptive energy management system.